Pembinaan Atlet Tarung Derajat di Satuan Latihan Se-Kota Semarang (Department of Physical Education, Sport, Health and Recreation, 2015)
Background problem on a survey of coaching accomplishments of athletes fighting unit exercises a degree inSemarang that quite proud of the achievements of the regional and national levels. This study uses descriptivequalitative research approach. Using observation and interviews. Results of studies have shown that 1) Stagesof development ranging from regulations performed well because it uses the print media as a tool for mass gain that much, the nursery was done quite as the nursery was started adulthood, enough talent scouting. 2) The program was developed with less exercise because exercise program is not made in writing, but the coach training program implemented either as a program in accordance with the objectives and scheduled exercise trainer 2-3 times a week. 3) Facilities and infrastructure owned enough but still need the addition. 4) Source of funds is less because only obtained from University funds even only from personal funds. 5) The organization is well established, but it is said not in accordance with their duties each because it is still run by one person or a few people. 6) Nutritional needs of athletes in training at the unit level are not available, but if it is at the branchlevel nutritional needs of athletes are already available and well met.